2023
DOI: 10.1186/s12933-023-01807-6
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue is an independent predictor and mediator of the progression of coronary calcification: a prospective sub-analysis of the GEA study

Abstract: Background Coronary artery calcium (CAC) improves cardiovascular event prediction. Visceral adipose tissue (VAT) is a cardiometabolic risk factor that may directly or through its related comorbidities determine the obesity-related risk. A clinical VAT estimator could allow an efficient evaluation of obesity-related risk. We aimed to analyze the effect of VAT and its related cardiometabolic risk factors on CAC progression. Methods CAC was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…A recent study by Antonio-Villa et al excluded patients with diabetes, similar to our study, and found that METS-VF strongly correlated with VFA (r=0.75) and effectively identified subjects with increased VFA (AUC 0.84), consistent with our findings. 31 These results suggest that the higher AUC values found compared to the Indian study may be attributed to differences in patient selection, and that METS-VF may be more suitable for identifying individuals at high cardiometabolic risk before the onset of metabolic complications. Notably, the group in which the METS-VF was developed excluded individuals with cardiovascular disease, those taking oral antidiabetic drugs other than metformin, and those with diabetic complications.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study by Antonio-Villa et al excluded patients with diabetes, similar to our study, and found that METS-VF strongly correlated with VFA (r=0.75) and effectively identified subjects with increased VFA (AUC 0.84), consistent with our findings. 31 These results suggest that the higher AUC values found compared to the Indian study may be attributed to differences in patient selection, and that METS-VF may be more suitable for identifying individuals at high cardiometabolic risk before the onset of metabolic complications. Notably, the group in which the METS-VF was developed excluded individuals with cardiovascular disease, those taking oral antidiabetic drugs other than metformin, and those with diabetic complications.…”
Section: Discussionmentioning
confidence: 71%
“…Visceral adipose tissue (VAT) served as a reliable marker for obesity in patients. Previous investigations consistently demonstrated elevated VAT in individuals with CHD ( 9 ). These studies typically employed computed tomography (CT) or magnetic resonance imaging (MRI) techniques to assess VAT levels.…”
Section: Introductionmentioning
confidence: 68%
“…Although various alternative indices for VAT based on simple anthropometric measurements, such as BMI, WHtR, WC, and waist-to-hip ratio, have been developed, these indices only provide a rough estimate of VAT content from the perspective of body fat distribution and do not adequately reflect the impact of VAT on metabolism [ 33 ]. METS-VF is a clinical estimator of VAT and is more accurate than other traditional visceral fat indices in estimating VAT [ 8 , 9 ]. Peng Yu et al showed that METS-VF was associated with a risk of chronic kidney disease (OR: 2.102, 95% CI: 1.653–2.674, P < 0.001) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this innovative index has been corroborated through validation with magnetic resonance imaging (MRI) and bioelectrical impedance analysis [ 8 ]. Neftali et al, reported that METS-VF identifies individuals with high VAT (VAT > 127 cm 2 for women, > 152.7 cm 2 for men), with an optimal area under the curve (AUC) (0.84, 95% CI: 0.81–0.87, P < 0.001) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%